Installation methods of precast concrete beams & columns, Campus UniSZA Tembila, Besut / Zakaria Abd Hamid - Abd Hamid, Zakaria (Universiti Teknologi MARA, Perak, 2018)
Industrialised Building Systems (JBS), also known as prefabrication, involves the manufacture of components off-site ready for installation. This report was prepared for the installation of IBS beams and columns at Library Building University Sultan Zainal Abidin in Tembila, Besut. The prime objective of building construction is to make sure that the performance of the building can be continues to the utmost throughout its design life. The objectives of the report areto identify the construction method of IBS beams and columns, determine the types of column and beam, determine the equipment and machineries that used for construction. The method of study used is interview, case study and literature review will be helped in making this report. To illustrate, the construction industry makes a vital contribution to the competitiveness and prosperity of the economy. A modem and efficient infrastructure is a key driver of productivity, and the construction industry has a major role in delivering the built infrastructure in an innovative and cost-effective way.